Cultural connections in early childhood: Learning through conversations between educators and children - Gwendalyn Webb (The Australian Journal of Indigenous Education, 2022)
This research aimed to explore the conversations between Aboriginal children and their educators in early childhood contexts. The research particularly focused on the relevance of these conversations for developing children’s identity. Participants were Aboriginal and non-Aboriginal children and educators, who participated in conversations in early childhood education and care (ECEC) contexts. Qualitative analysis of 26 interactions was conducted using an Indigenist approach. Analysis revealed a broad range of topics that were discussed in the interactions, with an overarching theme of social interaction and communication. Within this umbrella theme, educators focused on skill development and scaffolding children’s interactions and communication. This research highlights how educators in the ECEC context focus on developing children’s identity and skills through social interactions. Aboriginal educators integrated their cultural knowledge and experiences to develop Aboriginal children’s skills and scaffold their communication, in preparation for transition into a mainstream formal education system.